N-Shaped or Inverted N-Shaped EKC? The Role of Renewable and Non-Renewable Energy in Environmental Sustainability - Idroes, Ghalieb Mutig; Fakher, Hossein Ali; Hilal, Iin Shabrina; Wiranatakusuma, Dimas Bagus (Heca Sentra Analitika, 2026)
Climate change and global warming have become urgent challenges for all nations. Rapid population growth continues to raise energy demand, generating outputs that often create negative externalities and worsen environmental conditions. The Ecological footprint (EFP) and carbon dioxide (CO2) emissions are key indicators of environmental quality, with higher levels of these indicators generally reflecting a deterioration in environmental conditions. This study examines the effects of economic growth, renewable energy, and non-renewable energy on Indonesia’s environmental quality from 1965 to 2023 using the Autoregressive Distributed Lag (ARDL) approach, Granger causality and wavelet coherence analysis. The results reveal Environmental Kuznets Curve (EKC) dynamics, with an N-shaped EKC for the ecological footprint and an inverted N-shaped EKC for CO2 emissions. Capital formation reduces both EFP and CO2 emissions, while renewable energy significantly decreases CO2 emissions. Granger causality analysis shows directional relationships between economic growth, energy use, and environmental quality. Wavelet coherence results indicate strong co-movement between economic growth and non-renewable energy with EFP and CO2, confirming that fossil-fuel-driven expansion remains the main driver of degradation. In contrast, renewable energy and capital formation show negative coherence with environmental indicators, reflecting their growing role in mitigating ecological stress. Overall, the findings highlight Indonesia’s dual challenge of sustaining economic growth while curbing long-term environmental degradation, emphasizing the need for structural reforms, greater investment in renewable energy, and stronger environmental governance to ensure a sustainable development path.